MICROWAVE DEHYDRATION MODELLING OF TINCALCONITE - Coban, S.; Ozkarasu, B.; Senberber, F. T.; Kipcak, A. S.; Doymaz, I.; Derun, E. M. (YILDIZ TECHNICAL UNIV, 2018)
Boron is known element due to wide range of application areas. Microwave dehydration has more advantages than conventional dehydraion. Differ dehydraion mechanism, higher dehydraion rate and higher level of safety are some of this advantages. Furthermore, most of minerals give better result in microwave for temperature increase. Particle size, microwave power and sample mass are parameters which effect to dehydration directly. Structure of tincalconite is suitable for the investigation of dehydration behavior by microwave because of their five moles of crystal water. Tincalconite is a type of sodium borate mineral which has a white color, trigonal system and molecule formula of Na2B4O7 center dot 5H2O. Tincalconite contains 48.8% of boron oxide(B2O3) and 29.47% of structural water. In this study, dehydration behavior of tincalconite was studied with using microwave irradiation with the power level of 180 and 360 W. The kinetic parameters of reaction were determined by using the dehydration kinetic models of Lewis, Henderson and Pabis and Wang and Singh. Tincalconite and dehydrated tincalconite characterized by the techniques of X-ray diffraction (XRD) and Raman spectroscopy. According to the results obtained tincalconite was dehydrated successfully at the microwave power level of 360 W at 14 min, on the contrary at 180 W, only the 68% of the structural water was dehydrated. Among the models, which are applied only at 360 W, Wang and Singh model best fits the data with the coefficient of regression (R2) value of 0.9965.
Keywords: Tincalconite; Microwave; Dehydration; Modelling; XRD; Raman; KINETICS; ULEXITE; BEHAVIOR; ACID; Thermodynamics